2005
DOI: 10.1007/11538462_4
|View full text |Cite
|
Sign up to set email alerts
|

A Rounding Algorithm for Approximating Minimum Manhattan Networks

Abstract: Abstract. For a set T of n points (terminals) in the plane, a Manhattan network on T is a network N (T ) = (V, E) with the property that its edges are horizontal or vertical segments connecting points in V ⊇ T and for every pair of terminals, the network N (T ) contains a shortest l 1 -path between them. A minimum Manhattan network on T is a Manhattan network of minimum possible length. The problem of finding minimum Manhattan networks has been introduced by Gudmundsson, Levcopoulos, and Narasimhan (APPROX'99)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Kato et al [8] presented an O(n 3 )-time 2-approximation algorithm. Although the correctness proof of their algorithm is incomplete [3], the paper showed that checking the existence of a Manhattan path for O(n) specific pairs of points, instead of O(n 2 ) pairs in T × T , is sufficient for determining whether a given network is a Manhattan network. Following this idea, Benkert et al [1,2] proposed an O(n log n)-time 3-approximation algorithm.…”
Section: Historical Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Kato et al [8] presented an O(n 3 )-time 2-approximation algorithm. Although the correctness proof of their algorithm is incomplete [3], the paper showed that checking the existence of a Manhattan path for O(n) specific pairs of points, instead of O(n 2 ) pairs in T × T , is sufficient for determining whether a given network is a Manhattan network. Following this idea, Benkert et al [1,2] proposed an O(n log n)-time 3-approximation algorithm.…”
Section: Historical Reviewmentioning
confidence: 99%
“…They also described a mixed-integer programming (MIP) formulation of the MMN problem. After that, Chepoi et al [3] used the notion Pareto Envelope and a nice strip-staircase decomposition to divide the plane into several regions, which can be studied individually. Based on this idea, they proposed a 2-approximation rounding algorithm by solving the linear programming relaxation of the MIP.…”
Section: Historical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For t ≥ 1, a planar graph G is said to be a t-spanner of T if for all p, q ∈ T , there exists a path in G connecting p and q of length at most t times the distance between p and q. The MMN Problem for T is exactly the problem to compute the shortest 1-spanner of T under the L1-norm [3,4].…”
Section: Problem Descriptionmentioning
confidence: 99%